2018
DOI: 10.1177/0959683618777069
|View full text |Cite
|
Sign up to set email alerts
|

Maximum flood area during MIS 1 in the Almenara marshland (Western Mediterranean): Benthic foraminifera and sedimentary record

Abstract: The sedimentological and micropaleontological analysis of three mechanical cores in the marshland of Almenara (Valencian Community, Spain) has allowed the reconstruction of the Holocene evolution of this wetland. The cold and dry 8.2-ka event might be represented in Almenara by a massive carbonate precipitation bed, upon which mid- and late-Holocene sediments were subsequently deposited. The direct influence of sea-level changes has been recorded in the two cores (S-4 and S-5) located near the marsh barrier, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Large uncertainties are associated with the SLIPs and poor descriptions of the original data did not allow us to robustly assess the RSL history in this area, notably for the last 6000 years. A new dataset of dated estuarine facies (Carmona et al, 2016;Blázquez et al, 2017;Rodríguez-Pérez, 2018) has facilitated a significant advance in the definition of the mid-to late-Holocene RSL evolution of this coastal sector.…”
mentioning
confidence: 99%
“…Large uncertainties are associated with the SLIPs and poor descriptions of the original data did not allow us to robustly assess the RSL history in this area, notably for the last 6000 years. A new dataset of dated estuarine facies (Carmona et al, 2016;Blázquez et al, 2017;Rodríguez-Pérez, 2018) has facilitated a significant advance in the definition of the mid-to late-Holocene RSL evolution of this coastal sector.…”
mentioning
confidence: 99%
“…For most of the last 4000 years, coastal wetlands have no direct connection to the sea. In the case of the marshes of Almenara and Benicasim, the paleoecological studies (foraminifers and ostracods) show that they were oligohaline marshes only affected by small fluctuations in their water levels (Usera et al, 1996;Mediato, 2016;Blázquez et al, 2017Blázquez et al, , 2018Rodríguez-Pérez et al, 2018). These authors did not reach conclusive paleoecological data that allowed distinguishing relative changes in salinity of wetlands during the period.…”
Section: Introductionmentioning
confidence: 99%
“…They are typical features of the coastal plain landscapes of the Spanish Mediterranean coast: Mar Menor, Valencia lagoon, Oliva-Pego marsh, Almenara, Benicasim and Torreblanca-Cabanes marshes. Previous sedimentological, geomorphological and paleontological studies focused on their paleoenvironmental reconstruction during the Holocene (Dupré et al, 1988;Usera et al, 1996Usera et al, , 2002Mediato and Santisteban, 2006;Carmona and Ruiz, 2011;Marco-Barba et al, 2013, Carmona et al, 2016Mediato, 2016;Blázquez et al, 2017Blázquez et al, , 2018Rodríguez-Pérez et al, 2018;Ruiz-Pérez and Carmona, 2019;López-Belzunce et al, 2020). These studies concluded that the Holocene paleoenvironmental changes were related to the eustatic variations that took place since the Last Glacial Maximum and climate was a minor forcing of local interest.…”
Section: Introductionmentioning
confidence: 99%
“…A geological perspective is key for addressing this issue and stratigraphic studies can provide a long‐term view, useful for conservation and restoration strategies. In this respect, the subsurface sedimentary successions of the Mediterranean coastal plains represent invaluable archives containing the full set of bio‐sedimentary data able to provide insights on past ecosystem dynamics and associated forcing (Leorri et al ., 2006; Sacchi et al ., 2014; Zecchin et al ., 2014; Di Rita et al ., 2015; Bellotti et al ., 2016; Cearreta et al ., 2016; Ejarque et al ., 2016; Milli et al ., 2016; Rodríguez‐Pérez et al ., 2018; Revelles et al ., 2019; Seeliger et al ., 2019; Vella et al ., 2019). The integration of different fossil groups (e.g.…”
Section: Introductionmentioning
confidence: 99%